Beyond the Centre: Tracing Decentralization's Influence on Time-varying Fiscal Sustainability - António Afonso; José Alves; Jo\~ao Tovar Jalles; Sofia Monteiro (CESifo GmbH, 2024)
This paper explores the nuanced relationship between fiscal decentralization and fiscal sustainability. Employing panel data analyses, it scrutinizes how decentralization influences fiscal discipline across different governmental levels. Results for 185 countries show that while tax decentralization often hampers the degree of fiscal responsiveness, potentially due to misaligned local and national objectives and loss of scale efficiency, spending decentralization can enhance fiscal outcomes by promoting efficient resource allocation. These findings are contextualized within a broad range of economic and political environments, highlighting that the impacts of decentralization are contingent upon local capacities and overarching governance frameworks. Hence, we contribute to the understanding of fiscal policies' complexity in decentralized systems and offer significant policy insights for fiscal sustainability in varied administrative contexts.
Keywords: H11; H77; H72; H73; E62; C23; 330; panel data analysis; fiscal sustainability; decentralization; fiscal rules; political cycles; time-varying coefficients